The Supervision of Administrative Head on the Implementation of IT-Based Archiving at SMAN 1 Koto Salak - Oktavia, Reni; Agustian, Hesti; Andre, Lesis; Syam, Fadhli (The Future of Education Journal, 2025)
Supervision of the head of administration is the ability to supervise, guide, and direct the administrative staff to work in accordance with the rules that have been set. The supervisory role of the Head of Administration is very important in maintaining the security and confidentiality of data, as well as increasing efficiency and order in the management of archives at SMAN 1 Koto Salak Dharmasraya. Supervision of archive implementation is very important, not only to supervise but also to maintain the integrity of the archive so that it can be used in the long term. Archives refer to records of activities or events recorded in various forms and media, in accordance with the development of information and communication technology. Therefore, the problem to be studied in this research is, “How is the Supervision of the Head of Administration on the Implementation of IT-Based Archives at SMAN 1 Koto Salak”.This type of research is descriptive research with qualitative methods. The research subjects were the head of administration and administrative staff. Data analysis techniques are done by means of interviews, observation, and documentation. Data validity techniques are done by data triangulation.The results of this study are: a) to find out how the Implementation of IT-Based Archives which aims to manage, store and access documents in digital form, b) the advantages and disadvantages of IT-Based Archives, c) Supervision of the Head of Administration of the Implementation of IT-Based Archives at SMAN 1 Koto Salak which has three stages.